Synthesis and characterization of ceramic (alumina) membrane sheet - Idrees, M; Lim, Yan; Saidi, Hamdani (1995)
The objectives of this work are to synthesis ceramic alumina membranes by the moulding (pressing) process and to determine the effect of pressing force and the sintering temperature on the characteristics of the membrane. The membranes were characterized for the microstructure and pore size distribution by using Scanning Electron Microscope (SEM). The density and porosity of the membrane were measured by using water absorption measurement.Details of the study are available in full text article.